Augmented intelligence for open education: bridging the digital gap with inclusive design methods - Alvarez-Icaza, Inés; Huerta, Omar (Frontiers in Education, 2024)
Artificial Intelligence (AI) development with an inclusive vision will not happen without the design theory and committed practice, but neither can it be carried out from a biased in-a-silo design vision. Having as its primary goal to augment human capacities, it is crucial to overcome the bias produced by human fuzziness. The application of the DM4O design methodology enables the envisioning of different scenarios to conceptualize inclusive digital education platforms as key resources to bridge the digital gap for learners in a global context. Aligned with Sustainable Development Goal (SDG) number 4, the objective of this study is to identify potential higher education (Hi-Ed) students’ limitations when interacting with an open education digital platform (OE-DP), to propose a set of inclusive design guidelines. Following a mixed methods approach, this article sets the state of the art across a systematic literature review; then presents the DM4O design method as the data gathering tool; and finally reports the results of a survey application to capture the perceived limitations experienced by Hi-Ed students as users of an OE-DP. This study marks valuable insights for designers, educators, and institutional administrators, toward a digital transformation that promotes inclusive OE-DPs innovation in three dimensions: (a) inclusive guidelines for digital platforms; (b) a comprehensive list of interaction tasks suitable for digital platforms; and (c) the potential limitations that these platforms must cover during the design process.